Reclassification of the Candida haemulonii Complex as Candida haemulonii (C. haemulonii Group I), C. duobushaemulonii sp. nov. (C. haemulonii Group II), and C. haemulonii var. vulnera var. nov.: Three Multiresistant Human Pathogenic Yeasts - Cendejas-Bueno, E. (American Society for Microbiology, 2012)

(untitled)
The Candida haemulonii species complex is currently known as C. haemulonii groups I and II. Here we describe C. haemulonii group II as a new species, Candida duobushaemulonii sp. nov., and C. haemulonii var. vulnera as new a variety of C. haemulonii group I using phenotypic and molecular methods. These taxa and other relatives of C. haemulonii (i.e., Candida auris and Candida pseudohaemulonii) cannot be differentiated by the commercial methods now used for yeast identification. Four isolates (C. haemulonii var. vulnera) differed from the other isolates of C. haemulonii in the sequence of the internal transcribed spacer (ITS) regions of the nuclear rRNA gene operon. The new species and the new variety have a multiresistant antifungal profile, which includes high MICs of amphotericin B (geometric mean MIC, 1.18 mg/liter for C. haemulonii var. vulnera and 2 mg/liter for C. duobushaemulonii sp. nov) and cross-resistance to azole compounds. Identification of these species should be based on molecular methods, such as sequence analysis of ITS regions and matrix-assisted laser desorption ionization–time of flight mass spectrometry.